PENERAPAN METODE IMLA’ MANQUL PADA SISWA SMPQ DARUL FATTAH BANDAR LAMPUNG - Anwar, Khairil (Al Mufid, 2021)
This research is based on a lack of knowledge about Arabic writing skills, students do not have a basic knowledge and still lack of practice in writing Arabic. In this study, researchers used the Imla 'Manqul method, which is moving writing from certain media to textbooks and dictating it. The purpose of this research is "Knowing the improvement of Arabic and describing the improvement of writing skills using the imla method" manqul VII G grade students of SMP Quran Darul Fattah "". While in the research method, the researcher used classroom action research (PTK), with 25 students as the research subject and this study was conducted in 2 cycles with the subject of Aqsamul Kalimat. The results of this research are very significant. In the Pre-cycle the average value was 71.04, there was an increase in cycle I of 5.85% with an average value of 75.2, while from cycle I to cycle II increased by 15.02% with an average value of 86.52. So from the results of this study the researcher took the conclusion that the application of the imla 'manqul method can improve students' writing skills in learning Arabic.